2001
DOI: 10.3171/foc.2001.11.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chiari type I malformation in patients with and without syringomyelia: a consecutive series of 66 cases

Abstract: Object The authors describe the results of performing a standard posterior craniovertebral decompression and placement, if indicated, of a syringosubarachnoid shunt for the treatment of patients with Chiari I malformation with and without syringomyelia. Methods This is a retrospectively analyzed consecutive series of 66 patients (mean patient age 15 years, range 1–53 years). The uniform posterior craniov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
2
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(124 citation statements)
references
References 74 publications
10
96
2
9
Order By: Relevance
“…1,11,12,18,22,26,32,35,42 Children with CM-I have smaller posterior fossae than controls, 28,38,41,45 and in 1 study, patients with an associated syrinx had yet smaller posterior fossae than CM-I patients without a syrinx. 40 Syrinx has a strong association with scoliosis as well as motor and sensory symptoms.…”
Section: Discussionmentioning
confidence: 95%
“…1,11,12,18,22,26,32,35,42 Children with CM-I have smaller posterior fossae than controls, 28,38,41,45 and in 1 study, patients with an associated syrinx had yet smaller posterior fossae than CM-I patients without a syrinx. 40 Syrinx has a strong association with scoliosis as well as motor and sensory symptoms.…”
Section: Discussionmentioning
confidence: 95%
“…La realización de una descompresión de la fosa posterior con plastia dural, puede ser una buena opción para restaurar el espacio subaracnoideo en la fosa posterior 3,24 .…”
Section: Craniectomía Suboccipital Con Duroplastiaunclassified
“…Según las series consultadas, la evolución clínica suele ser favorable, con resolución o disminución de los síntomas entre un 75% y un 100% de los pacientes independientemente de la técnica utilizada 3,21,22 . Aunque hay series de pacientes intervenidos sin duroplastia (incluyendo niños y adultos) que reportan porcentajes de mejoría equivalentes a los de las series en las que la cirugía incluía la duroplastia 9,22,27 , la mayor parte de los autores coinciden en afirmar que los mejores resultados se obtienen realizando la craniectomía suboccipital acompañada de duroplastia 7,8,11,24,26 .…”
Section: Evolución Clínicaunclassified
See 1 more Smart Citation
“…This results in decompression of the cerebellar tonsil restores the normal cerebrospinal fluid flow [7]. Several studies have shown the effectiveness of PFD for treatment of syrinx in these patients: 50-100% experienced a decrease in size of spinal cavity [5,[8][9][10][11]. Recently, Wetjen et al [12] performed a serial magnetic resonance imaging (MRI) study to establish the time course for syrinx resolution after PFD and found that the syrinx began to resolve within 3.6 months after decompression and continued to decrease for months to years.…”
Section: Introductionmentioning
confidence: 99%